Wikowie. Neowiktoriańskie spojrzenie na Epokę Diamentu Neala Stephensona - Zielonka, Konrad (Zagadnienia Rodzajów Literackich, 2025)
The aim of this article is to present the principles of the neo-Victorian movement using the example of the Neal Stephenson’s novel The Diamond Age. In the futuristic world created by the author, nineteenth-century Victorianism is revived as an ideology that shapes the social structure of the “Vickys,” one of the most influential social groups. The novel can be seen as an example of literature that (re)interprets the Victorian era, both in terms of its aesthetic and moral dimensions. At the center of this study is the neo-Victorian community — a futuristic society that consciously reconstructs nineteenth century Victorian values, aesthetics, and moral codes in response to the identity crisis and moral decline of the twentieth century. Neo-Victorianism is presented here as a tool for building a new social and ethical order. Even the choice of aesthetics — at first glance a nostalgic return to the era — carries a specific, deeply encoded message that is understood by both Victorian and neo-Victorian societies. The Diamond Age can be considered a representative example of neo-Victorian fiction. Its core lies in a return to nineteenth-century ideals — not through a literal return to the “Age of Steam,” but through a renaissance of Victorian values within a cyberpunk vision of the near future. The analysis demonstrates how the author (re)constructs nineteenth-century cultural patterns, aesthetics and value systems within a futuristic setting. The discussion begins with a reflection on the nature of the Neo-Victorian movement and considers its relevance in the context of broader cultural and identity transformations.